Pengaruh Variasi Penguat Biokomposit Serat Kulit Buah Pinang/Serat Pelepah Batang Pisang/Matriks LDPE Pada Perendaman NaOH Terhadap Kekuatan Bending Dan Penyerapan Air - Candra Ari Wiguna, I Gede Dikki; Kencanawati, Cok Istri Putri Kusuma; Priambadi, I Gusti Ngurah (Teknik Desain Mekanika; Vol 11 No 2 (2022): April 2022 : Teknik Desain Mekanika, 2022)
Abstract Indonesia's abundance natural resources makes Indonesia can be potential leader in the development of natural fiber-based materials especially biocomposites, the advantage biocomposite over syntetic material is they have minimal environmental impact. Plastic takes a long time to decompose naturally. Researchers tried to use plastic as a matrix and natural fibers as reinforcement with purpose to utilizing the potential of Indonesia's natural resources and minimize the negative impact of plastic on the environment. In this study use volume fraction of areca skin fiber:Banana stem fiber:LDPE such as 10%:0%:90(S1), 0%:10%:90%(S2), 7.5%:2,5%: 90%(S3), 5%:5%:90%(S4), 2.5%:7.5%:90%(S5). The biocomposite was made using ASTM D790-03 as reference for the Bending test and ASTM D570-98 for the Water Absorption test. The highest bending stress is found in variations S3 with 11.93 MPa, the highest bending strain is found in variations S3 with 0.0556 and the highest modulus of elasticity is found in variations S2 with 563.04 MPa. The water absorption test showed that the variation with the lowest water absorption was in the S3 variation of 6.709% and the variation with the highest water absorption was found in the S2 variation with a value of 10.008%. The combination of Fiber and LDPE Matrix was observed through micro photo observations. Keywords: Areca Skin Fiber, Banana Stem Fiber, Low Density Polyethylene, Flexural Test, Water Absorption Test, Micro Photo.